Dose response of xylanase enzyme on ileal viscosity, digestibility of nutrients, and performance of broiler chickens fed wheat-based diets - J.I. Vargas; J.P. Gulizia; J.R. Hernandez; C.T. Simões; E.G. Guzman; J. Lee; R. Adhikari; S.E. Han; W.J. Pacheco (Journal of Applied Poultry Research)
SUMMARY: This experiment investigated the dose-response effect of xylanase inclusion on growth performance, ileal digesta viscosity, and nutrient digestibility of broilers fed wheat-based mash diets from 1 to 42 d of age. A total of 1,500-day-old YPM × Ross 708 male broilers were randomly sorted in 50 floor pens and assigned to 5 treatments with 10 replicates per treatment. For each feeding phase, a positive control (PC) was formulated to meet the nutrient requirements of broilers, a negative control (NC) was formulated to contain 100 kcal/kg less AMEn than the PC, and 3 additional treatments were created by including xylanase to the NC at 1,200 (NC + 1,200), 2,400 (NC + 2,400) and 4,800 (NC + 4,800) U/kg. Feed intake, BW, and mortality corrected FCR were determined at 14, 28, and 42 d of age. Ileal digesta was collected from 7 birds per pen on d 28 to analyze nutrient digestibility and viscosity. In addition, the severity of footpad dermatitis and litter moisture were evaluated at 42 d of age. Data were analyzed as a randomized complete block design using the ANOVA procedure and means were separated by Tukey's HSD test, considering statistical significance at P ≤ 0.05. Broilers fed the NC + 4,800 U/kg diet exhibited a higher BW at 14 (P < 0.001) and 28 (P < 0.05) d of age in comparison to the NC. Similarly, improvements on FCR from 1 to 28 (P < 0.001) and 1 to 42 (P < 0.001) d of age were observed with a xylanase dose of 1,200 U/kg and higher, in comparison to the NC. In addition, broilers fed the NC supplemented with xylanase at all doses effectively reduced (P < 0.001) ileal digesta viscosity in comparison to the NC. Finally, xylanase supplementation at a dose of 2,400 U/kg to the NC increased CP (P < 0.01), and apparent ileal total amino acid digestibility (P < 0.001) compared to the NC. Overall, supplementation of mash wheat-based diets with incremental doses of xylanase improved broiler performance and nutrient digestibility while reducing ileal digesta viscosity.